(untitled) (American Journal of Islam and Society, 2004)
This paper focuses on the dilemmas that al-Afghani and Rida encountered while advocating and working for political reform: Whenever they fought the tyranny of Muslim rulers, they were targeted, and usually defeated, by colonial powers. And once they began to struggle against colonialism and call for Muslim unity, they were victimized and had their plans aborted by authoritarian Muslim rulers. This was a lesson for later Islamic political movements, as they had to identify clearly, and on solid theoretical bases, their target of reform and the real enemy, and prioritize their goals and methods of reform.